Pedagogy, epistemology and training. Actuality of the pedagogical question - Espinel, Oscar; Pulido, Oscar (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Wondering about teaching practice, its forms and possibilities implies asking about the meanings of pedagogy and the ways it is assumed in daily school life. Far from seeking closed definitions, this article contributes some elements to the discussion as an invitation to situate the grounds of the contemporary question about pedagogy and its necessary updating. To this end, it begins by dealing with the relations between education, pedagogy and didactics, and then addresses the epistemological question regarding pedagogy, its link with philosophy and the place of the teacher. Finally, pedagogy is recognized as a field in and of constitution.